Transformasi Pembelajaran Pendidikan Agama Islam Melalui Active Learning : Kajian Atas Metode Card Sort, The Power of Two, dan Snowballing - Agus Royo; Dian Ika Safitriana; Rahmat Kamal (Lembaga Pengembangan Kinerja Dosen, 2025)
Islamic Religious Education (IRE) plays a crucial role in shaping the moral character of students at the elementary school level. However, learning methods used in IRE classrooms often remain conventional and teacher-centered, resulting in low student engagement and limited understanding of religious material. In response to the educational demands of the 21st century, a transformation in learning strategies is necessary. This study explores the implementation of active learning methods Card Sort, The Power of Two, and Snowballing as innovative approaches to revitalize IRE instruction. Using a qualitative descriptive method, data were gathered through classroom observations, in-depth interviews with teachers and students, and supporting documentation. The findings reveal that Card Sort enhances students’ ability to visually organize and connect religious concepts, The Power of Two facilitates deeper comprehension through peer discussion, and Snowballing promotes collaborative knowledge construction in stages. These methods contribute to a more interactive, student-centered, and meaningful learning process. Moreover, the integration of these strategies helps improve students' critical thinking, communication, and social-emotional skills while strengthening their internalization of Islamic values. Despite challenges such as instructional planning and classroom management, active learning techniques offer promising potential to transform IRE learning into a dynamic and participatory experience. The study provides practical recommendations for educators and school administrators to develop more effective and engaging IRE strategies.